Development and validation of spectrophotometric method for the determination of DPP-4 inhibitor, sitagliptin, in its pharmaceutical preparations - Sekaran, Chandra Bala; Rani, Avula Prameela (Eclética Química, 2010)
A simple, sensitive and reproducible spectrophotometric method was developed for the determination of sitagliptin phosphate in bulk and in pharmaceutical formulations. The proposed method is based on condensation of the primary amino group of sitagliptin phosphate with acetyl acetone and formaldehyde producing a yellow colored product, which is measured spectrophotometrically at 430nm. The color was stable for about 1 hour. Beer’s law is obeyed over a concentration range of 5-25 μg/ml. The apparent molar absorptivity and Sandell sensitivity values are 1.067 x 104 Lmol-1cm-1 and 0.0471 μgcm-2 respectively. All the variables were studied to optimize the reaction conditions. No interference was observed in the presence of common pharmaceutical excipients. The validity of the method was tested by analyzing sitagliptin phosphate in its pharmaceutical preparations. Good recoveries were obtained. The developed method was successfully employed for the determination of sitagliptin phosphate in various pharmaceutical preparations.